E0211 Si Miao Yong An decoction promotes atherosclerotic plaque stability in vulnerable plaque rabbits. (17th November 2010) - Peng, Li; Zhang, Jun-Ping; Li, Ming; Li, Liang-Jun; Xu, Ying-Zhi; Zhang, Guang-Yin; Yang, Cui; Zhou, Ya-Nan
Abstract : Background: Si Miao Yong An decoction and its medicine Mailuoning injection are proved-effect medicine treating ischaemic cardiovascular disease, but whether it can stabilise the atherosclerotic plaque is currently no clear conclusions. We want to explore the role of Si Miao Yong An decoction interventing on rabbit aortic atherosclerotic plaque instability. Methods: Japanese white rabbits were divided into control group, model group, Simvastatin group and Si Miao Yong An group. The animals were killed at the end of the experiment. The pathological changes in aortic was observed by HE colouring, masson staining and oil red staining. CRP, MMP-9, ICAM-1 and NF-κB/p65 were tested with ELISA, immunochemistry or RT-PCR. Results: Pathological observation showed that thin fibrous cap and big lipid core area was the feature of plaque in the model group. The main components of plaque were macrophages and fat, collagen and actin content of plaque was little, which had showed the pathological characteristics of unstable plaque. We found atherosclerotic lesions of aorta in two drug groups were lighter than in model group (p<0.05 or p<0.01). Si Miao Yong An decoction was superior to Simvastatin in increasing fibrous cap thickness and actin content, reducing lipid core area and MMP-9 expression in plaque (p<0.01). However, there was no significant difference between the two drugs in reducing NF-κB/p65 and ICAM-1 mRNA expression (p>0.05). Conclusions: Based on these results, we believe that Si Miao Yong An decoction can promotes atherosclerotic plaque stability by fighting against inflammatory, inhibiting matrix degradation and lipid deposition.